2014
DOI: 10.1099/vir.0.058149-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Merkel cell polyomavirus based on full-length LT and VP1 gene sequences derived from neoplastic tumours in Japanese patients

Abstract: Most Merkel cell polyomavirus (MCPyV) gene sequences have been reported from Western countries and few data are available for the virus sequences from other geographical areas, especially Asia. Thus, we performed phylogenetic analyses based on the nucleotide sequences of the full-length large T-antigen (LT) and viral protein 1 (VP1) genes derived from a variety of cancers in Japanese patients and compared them with sequences from Caucasians. The LT and VP1 gene-based phylogenetic trees identified two main gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Looking at figure 1 , it appears that the MCPyV LT-ag polymorphic profile has a geographical influence, as observed by others [24,25] . However, the role of intra-host selective forces in shaping MCPyV DNA remains to be determined, as well as the possibility that certain strains might influence the course of the infection [25] .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Looking at figure 1 , it appears that the MCPyV LT-ag polymorphic profile has a geographical influence, as observed by others [24,25] . However, the role of intra-host selective forces in shaping MCPyV DNA remains to be determined, as well as the possibility that certain strains might influence the course of the infection [25] .…”
Section: Discussionmentioning
confidence: 50%
“…However, the role of intra-host selective forces in shaping MCPyV DNA remains to be determined, as well as the possibility that certain strains might influence the course of the infection [25] . It should be considered that our apparent mutation profile may also have been influenced by methodological differences between studies, especially the sampling process, number of samples and the characteristics of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Two clades, or phylogenetic groups, of MCPyV DNA sequences have been characterized from different geographical regions . Phylogenetic analyses derived from a variety of cancers in Japanese patients in comparison with sequences from white populations have confirmed that most of the MCPyV strains in Japan form a separate clade, unique from strains in white populations . There is a possibility that different MCPyV strains are prevalent in geographically distinct human populations, a feature comparable with JC virus and BK virus, whose worldwide sequence divergence patterns have been shown to resemble ‘out of Africa’ models of prehistoric human migration …”
Section: Merkel Cell Polyomavirusmentioning
confidence: 99%
“…To date, it is the only HPyV that has been shown to mediate tumorigenesis . Two clades, or phylogenetic groups, of MCPyV DNA sequences have been characterized from different geographical regions . Phylogenetic analyses derived from a variety of cancers in Japanese patients in comparison with sequences from white populations have confirmed that most of the MCPyV strains in Japan form a separate clade, unique from strains in white populations .…”
Section: Merkel Cell Polyomavirusmentioning
confidence: 99%
“…Hashida et al [20] reported interesting findings from phylogenetic analyses based on the nucleotide sequences of the full-length MCPyV LT gene derived from cancer samples including MCC and lung cancer in Japanese patients and those from MCC samples in Caucasian patients. The phylogenetic analyses identified two main genetic clades.…”
mentioning
confidence: 99%